2017
DOI: 10.1371/journal.pgen.1007090
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of transcription elongation in response to osmostress

Abstract: Cells trigger massive changes in gene expression upon environmental fluctuations. The Hog1 stress-activated protein kinase (SAPK) is an important regulator of the transcriptional activation program that maximizes cell fitness when yeast cells are exposed to osmostress. Besides being associated with transcription factors bound at target promoters to stimulate transcriptional initiation, activated Hog1 behaves as a transcriptional elongation factor that is selective for stress-responsive genes. Here, we provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 51 publications
(80 reference statements)
6
15
0
Order By: Relevance
“…This study and previous stress tolerance investigations have identified several dozen to several hundred significant gene expression changes after stress exposure in budding yeasts 13,[16][17][18]28 . Despite analysis of stress-responsive genes in several robust species, rational engineering of robust strains remains difficult.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…This study and previous stress tolerance investigations have identified several dozen to several hundred significant gene expression changes after stress exposure in budding yeasts 13,[16][17][18]28 . Despite analysis of stress-responsive genes in several robust species, rational engineering of robust strains remains difficult.…”
Section: Discussionsupporting
confidence: 60%
“…These results suggest that several genes from different gene families may contribute additively to robustness and/or that stress genes may exist as duplicates, as is the case for antifreeze protein genes in artic yeasts 15 . Thus, researchers have employed systems biology to characterize the transcriptome and/or proteome-wide stress-induced changes 13,14,[16][17][18] . These approaches have identified biological processes that exhibit altered expression in response to stress exposure, which build upon and relate to extensive previous research into gene functions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This study and previous stress tolerance investigations have identified dozens to hundreds of significant gene expression changes after stress exposure in budding yeasts 13,[16][17][18]28 . Despite analysis of such stress-responsive genes in multiple species, rational engineering to further enhance robustness of industrial yeast strains remains difficult.…”
Section: Discussionsupporting
confidence: 52%
“…These results suggest that multiple genes from different gene families may contribute additively to robustness and/or that stress genes may exist as duplicates, as is the case for antifreeze protein genes in artic yeasts 15 . Thus, researchers have employed systems biology to characterize the transcriptome and/or proteome-wide stressinduced changes 13,14,[16][17][18] . These approaches have identified biological processes that exhibit altered expression in response to stress exposure, which builds upon and relates to previous research into gene functions (e.g., GO term enrichment analysis).…”
mentioning
confidence: 99%
“…Shaping the Transcriptional Landscape through MAPK Signaling DOI: http://dx.doi.org /10.5772/intechopen.80634 Moreover, Hog1 phosphorylates the Spt4 elongation factor to regulate RNA Pol II processivity to stimulate elongation efficiency at stress-responsive genes [55]. As happens during initiation, Hog1 recruits other protein complexes with specific enzymatic activities such as deubiquitinase (Ubp3) to ensure the proper production of stress-responsive genes [50].…”
Section: Transcription Elongationmentioning
confidence: 99%